2008
DOI: 10.1042/bj20071318
|View full text |Cite
|
Sign up to set email alerts
|

Rab10 in insulin-stimulated GLUT4 translocation

Abstract: In fat and muscle cells, insulin stimulates the movement to and fusion of intracellular vesicles containing GLUT4 with the plasma membrane, a process referred to as GLUT4 translocation. Previous studies have indicated that Akt [also known as PKB (protein kinase B)] phosphorylation of AS160, a GAP (GTPase-activating protein) for Rabs, is required for GLUT4 translocation. The results suggest that this phosphorylation suppresses the GAP activity and leads to the elevation of the GTP form of one or more Rabs requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 27 publications
7
101
1
Order By: Relevance
“…These data all support the hypothesis that AS160 negatively regulates the activity of Rab protein(s) involved in GLUT4 translocation. Recently, it has been suggested that Rab10 is the Rab protein downstream of AS160, since introduction of the constitutively active Rab10 (Rab10 Q67L ) increases the PM fraction of GLUT4 in the absence of insulin stimulation, and knockdown of Rab10 retards insulin-stimulated GLUT4 translocation [8,9]. These findings further support the existence of a negative regulatory mechanism between AS160 and Rab protein(s).…”
Section: Introductionsupporting
confidence: 70%
“…These data all support the hypothesis that AS160 negatively regulates the activity of Rab protein(s) involved in GLUT4 translocation. Recently, it has been suggested that Rab10 is the Rab protein downstream of AS160, since introduction of the constitutively active Rab10 (Rab10 Q67L ) increases the PM fraction of GLUT4 in the absence of insulin stimulation, and knockdown of Rab10 retards insulin-stimulated GLUT4 translocation [8,9]. These findings further support the existence of a negative regulatory mechanism between AS160 and Rab protein(s).…”
Section: Introductionsupporting
confidence: 70%
“…The interconnection of Rab GTPases in cascades may incorporate entire circuits involved in specific physiological responses, connecting exocytosis to cargo return via endocytosis. This is particularly evident in specialized pathways such as the coordinate function of exocytic and endocytic Rab GTPases in transport to the primary cilium, insulin-stimulated GLUT4 vesicle secretion, and recycling, as well as responses to metabolic stress that trigger autophagy or lipid droplet formation (Sano et al 2008;Longatti and Tooze 2009;Murphy et al 2009;Ward et al 2011;Westlake et al 2011;Chen et al 2012;Longatti et al 2012;Reed et al 2013). …”
Section: Endosome Compartmentalization Via Rab Gtpasesmentioning
confidence: 99%
“…Interestingly, studies have revealed that in adipose cells, Rab10 appears to be the isoform regulated by AS160 (Sano et al 2007(Sano et al , 2008 whereas in muscle cells, the isoforms are Rabs 8A and 14 (Ishikura et al 2007). These findings are based on: a) their ability, when over-expressed as GTP-locked mutants, to rescue the inhibitory effects on GLUT4 trafficking of either the dominant-negative AS160 4P mutant or of siRNA-mediated AS160 knockdown, and b) the effect of siRNA-mediated depletion of the Rab isoform on insulinstimulated glucose transport in adipocytes or muscle cells.…”
Section: Akt Substrate Of 160 Kdamentioning
confidence: 99%
“…This process has recently been shown to involve the insulin-stimulated phosphorylation of Munc18c on Tyr219, which is thought to induce a change in the binding specificity of Munc18c from syntaxin4 to Doc2b (Jewell et al 2008), a double C2 domain-containing protein that has been identified as a positive regulator of exocytic vesicle fusion in both adipocytes and adrenal chromaffin cells (Ke et al 2007, Friedrich et al 2008, Sano et al 2008, Fukuda et al 2009). Other syntaxin4 binding proteins that appear to function as negative regulators of GLUT4 vesicle fusion include Synip (Min et al 1999) and Tomosyn ( (Widberg et al 2003); these are not included in Fig.…”
Section: Protein Complexes Involved In Docking and Fusion Of Glut4 Vementioning
confidence: 99%